2004
DOI: 10.1289/ehp.6499
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between blood ethylenethiourea and thyroid gland disorders among banana plantation workers in the Philippines.

Abstract: Ethylenebisdithiocarbamates (EBDCs) are metabolized into ethylenethiourea (ETU), a possible human carcinogen and an antithyroid compound. In this study our goal was to correlate ETU levels with the incidence of thyroid gland disorders among banana plantation workers exposed to EBDC. We randomly selected 57 directly exposed workers and 31 indirectly exposed workers from four banana plantations and 43 workers from an organic farm; all subjects underwent complete medical examinations and laboratory tests. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 16 publications
1
33
0
Order By: Relevance
“…There was no significant difference in T 4 concentrations between these two groups. Studies conducted with banana plantation workers in the Philippines did not find any difference in TSH and T 4 levels between workers and the control group (Panganiban et al, 2004). However, nutritional iodine intake as assessed by urinary iodine concentration was higher in the workers than in the control group.…”
Section: Human Health Effectsmentioning
confidence: 65%
See 2 more Smart Citations
“…There was no significant difference in T 4 concentrations between these two groups. Studies conducted with banana plantation workers in the Philippines did not find any difference in TSH and T 4 levels between workers and the control group (Panganiban et al, 2004). However, nutritional iodine intake as assessed by urinary iodine concentration was higher in the workers than in the control group.…”
Section: Human Health Effectsmentioning
confidence: 65%
“…These studies are outlined in Table II. The assessment of the workers' exposure, based on ETU concentrations in urine, has been done in Mexico in tomato growing areas (Steenland et al, 1997), in areas of floriculture in Ecuador (Colosio et al, 2003), in banana plantations in the Philippines (Panganiban et al, 2004), vineyards in Italy Corsini et al, 2005;Colosio et al, 2007;Fustinoni et al, 2008), in grains, tobacco, vegetable and cut flower areas in Thailand (Panuwet et al, 2007), potato farms in Finland, , in the flower bulb growing industry in the Netherlands and in vegetable growing areas in Bulgaria . These studies have shown that the concentration of ETU in urine of exposed workers reflects the type of activity on the farm, the use of personal protective equipment such as gloves, respirators, plastic suits and boots, and the level of mechanization and training.…”
Section: Exposure Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their chelating properties, the dithiocarbamates (DTCs) modify cellular metabolism by their direct interactions with different molecules such as signaling proteins, peptides and enzymes, and influence the oxido-reductive metabolism of the cells (Vohr, 2012). Carcinogenicity of DTCs, including mancozeb, is due to their metabolite -2-imidazolidene thion (ethylene thiourea, ETU), which causes thyroid and pituitary tumors (Houeto et al, 1995;Panganiban et al, 2004;Axelstad et al, 2011).…”
mentioning
confidence: 99%
“…ETU was earlier classified by the International Agency for Research on Cancer as possibly carcinogenic to humans (group 2B), but, in 2001, it was reclassified into group 3 (not classifiable as to its carcinogenicity in humans) (11). This reclassification has been disputed (12), and published studies indicate that occupational exposure to ETU resulting from mancozeb use may perturb thyroid homeostasis (3,(13)(14)(15).…”
mentioning
confidence: 99%